80 TAHUN NEGARA HUKUM: REFLEKSI ATAS UPAYA PENEGAKAN HUKUM BERKEADILAN DAN BERLANDASKAN PANCASILA MENUJU INDONESIA EMAS 2045 - Udiyo Basuki (Fakultas Hukum Universitas Janabadra, 2025)
The day after Indonesia proclaimed its independence on August 17, 1945, the Indonesian constitution, the 1945 Constitution, officially came into effect on August 18, 1945. Several of its provisions affirmed Indonesia's status as a state based on law. The proclamation itself, meaning